2015
DOI: 10.1104/pp.15.00689
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for Functional Divergence and Decay of a Transcription Factor Derived from Whole-Genome Duplication in Arabidopsis thaliana

Abstract: Functional divergence between duplicate transcription factors (TFs) has been linked to critical events in the evolution of land plants and can result from changes in patterns of expression, binding site divergence, and/or interactions with other proteins. Although plant TFs tend to be retained post polyploidization, many are lost within tens to hundreds of million years. Thus, it can be hypothesized that some TFs in plant genomes are in the process of becoming pseudogenes. Here, we use a pair of salt tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 140 publications
1
20
0
Order By: Relevance
“…By combining these data together, although a common expression pattern for Class I and Class II F3'Hs across these monocot species can not be drawn at the moment, a transcriptional divergence for the two F3'H lineages may be proposed. The observation of gene functional divergence at both protein structural and gene transcriptional level have been reported in many plant gene families [56][57][58], and consolidated the theory of gene evolution via duplication [22,23]. In this study, the expression of different F3'H paralogs may have evolved a species-specific profile, meeting the particular environmental challenges faced by different plants.…”
Section: Discussionmentioning
confidence: 55%
“…By combining these data together, although a common expression pattern for Class I and Class II F3'Hs across these monocot species can not be drawn at the moment, a transcriptional divergence for the two F3'H lineages may be proposed. The observation of gene functional divergence at both protein structural and gene transcriptional level have been reported in many plant gene families [56][57][58], and consolidated the theory of gene evolution via duplication [22,23]. In this study, the expression of different F3'H paralogs may have evolved a species-specific profile, meeting the particular environmental challenges faced by different plants.…”
Section: Discussionmentioning
confidence: 55%
“…; Lehti‐Shiu et al . ). Although this study focuses only on coding sequences, a loss of function phenotype could also be achieved through mutation in regulatory regions (Alonso‐Blanco et al .…”
Section: Discussionmentioning
confidence: 97%
“…The comparison of maize, sorghum, and rice which differ in their number of MYB31/42 ohnologs provided an opportunity to investigate the consequences of regulatory network evolution following WGD events 37 38 39 40 41 42 . In general the fate of duplicated genes following WGD is poorly understood but an RNA-seq study of 18,000 duplicated genes in soybean revealed that about half of all genes and especially TFs were differentially expressed and had undergone expression sub-functionalization 40 .…”
Section: Discussionmentioning
confidence: 99%